2021
DOI: 10.5937/ffr48-34434
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Serbian consumers towards different pepper fruits

Abstract: Pepper (Capsicum annuum L.) is one of the major vegetable species in the world. In Balkan cuisines, as well as in Serbia, pepper has a very diverse use. Knowledge about consumer preferences is of great importance for a breeding process as well as in the market-orientated production. Because of the lack of information about consumer preferences towards pepper types, in the Serbian market, the present research was conducted. Four hundred and two participants, classified into groups, according to gender, age and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In Serbia, the main characteristics of peppers were determined. The obtained research results showed that the most popular type of bell pepper was kapija, while babura was the second type chosen, and the favorite color was red, although consumers preferred medium-hot fruits (Danojević et al, 2021) [22].…”
Section: Introductionmentioning
confidence: 96%
“…In Serbia, the main characteristics of peppers were determined. The obtained research results showed that the most popular type of bell pepper was kapija, while babura was the second type chosen, and the favorite color was red, although consumers preferred medium-hot fruits (Danojević et al, 2021) [22].…”
Section: Introductionmentioning
confidence: 96%
“…In order to select genotypes with above mentioned characteristics, the aim of this study was to evaluate 10 pepper lines of light-yellow tomato shape pepper fruit type. Although there are a lot of lines of this type with green fruits in IFVCNS pepper breeding collection, such genotypes were not used in this study because consumers in Serbia prefer red or light-yellow and yellow fruits more than green (Danojević et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…A major constraint in its production is determining the appropriate maturity stage, which is difficult even for fruit with similar physical traits during harvest [5,8]. Immature fruits (onset of turning color) may have unacceptable qualities, while whole-colored fruits lose their attractiveness and firmness, becoming soft in texture within a short time, influencing postharvest quality and consumer preference [9][10][11].…”
Section: Introductionmentioning
confidence: 99%